Peramalan Beban Puncak Transformator dengan Metode Dekomposisi di Gardu Induk 150 KV Weleri - Prasetyo Wahyu Aji Ritabin; Sri Arttini Dwi P. (Politeknik Kampar, 2025)
Electrical energy is essential for modern life, with demand increasing every year. Therefore, the development of electric power systems, including energy supply, transmission, and distribution, needs to be well planned. Transformers in substations play a vital role in converting high voltage of 150 kV to medium voltage of 20 kV to be distributed to customers. However, transformers that experience overloading can cause problems. According to the Directors' Circular Letter Number 0017.E/DIR/2014, the ideal transformer loading should be between 60% and 80%. Therefore, it is important to keep the transformer operating within safe limits to prevent disruption or damage to the electricity distribution system. One step to prevent transformer damage is to forecast peak loads in the future. There are many load forecasting methods that can be used. In this study, load forecasting was carried out using the simple linear regression method and the trend decomposition method. After the load forecasting is carried out, the accuracy of each method will be compared by calculating the MAPE value.